Reinventing Central Tax Administration: a Systematic Literature Review on Digital Tax Transformation and Compliance Enhancement in 2020–2025 - Rizkina, Miftha (Ridwan Institute, 2025)
This study provides a systematic literature review of recent developments in central tax administration, with a specific focus on digital tax transformation, compliance enhancement, and policy reform during the period 2020–2025. The main objective of this research is to synthesize existing empirical and theoretical studies to identify key trends, challenges, and best practices in modern tax administration systems. The novelty of this paper lies in its integration of global tax digitalization trends with compliance behavior theory to propose a new conceptual framework, namely the Integrated Digital Compliance Model (IDCM). This model emphasizes the interaction between digital infrastructure, taxpayer behavior, regulatory enforcement, and institutional capacity. The review findings indicate that the implementation of digital tax ecosystems—such as e-filing, e-invoicing, real-time reporting systems, and AI-driven compliance monitoring—has significantly improved voluntary compliance, reduced tax evasion, and lowered administrative and compliance costs for both tax authorities and taxpayers. Furthermore, the study finds that technology-driven enforcement mechanisms enhance transparency, data accuracy, and risk-based audit effectiveness. However, challenges related to data security, digital inequality, and institutional readiness remain critical issues, particularly in developing countries. This study contributes to the tax administration literature by identifying existing research gaps and proposing future research agendas. The findings are expected to provide practical insights for policymakers and tax authorities in designing effective, inclusive, and sustainable digital tax reforms in both developing and developed economies.